2017
DOI: 10.1051/itmconf/20171201013
|View full text |Cite
|
Sign up to set email alerts
|

LSTM-Based Temperature Prediction for Hot-Axles of Locomotives

Abstract: Abstract:The reliability of locomotives plays a central role for the smooth operation of railway systems. Hot-axle failures are one of the most commonly found problems leading to locomotive accidents. Since the operating status of the locomotive axle bearings can be distinctly reflected by the axle temperatures, online temperature monitoring has become an essential way to detect hot-axle failures. In this work, we explore the feasibility of predict the hot-axle failures by identifying the temperature from pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In comparison to the traditional modeling techniques, such as statistical methods, ML algorithms are popular when working with time series data [7,8]. RNNs, such as Long Short-Term Memory (LSTM) [9] and its derivative Gated Recurrent Units (GRU) [10], are dominant ML algorithms for modeling temporal correlations from a dataset [7,8,[11][12][13]. This is because of their ability to learn long-range dependencies in sequential data better than conventional RNNs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the traditional modeling techniques, such as statistical methods, ML algorithms are popular when working with time series data [7,8]. RNNs, such as Long Short-Term Memory (LSTM) [9] and its derivative Gated Recurrent Units (GRU) [10], are dominant ML algorithms for modeling temporal correlations from a dataset [7,8,[11][12][13]. This is because of their ability to learn long-range dependencies in sequential data better than conventional RNNs.…”
Section: Related Workmentioning
confidence: 99%
“…The paper shows that an LSTM model outperforms existing baselines including the Feedforward Neural Networks (FNNs) with hand-engineered features. In [11], an LSTM is used to predict the temperature of the axle bearing of a railway. The authors trained an LSTM model with the historical temperature data along with other physical properties, such as pressure, velocity of the train, etc.…”
Section: Related Workmentioning
confidence: 99%
“…In the work done by Ma et al [13], it was found that the velocity, the carrying capability and the ambient temperature affect the axle temperature, while the traction has less effect. Luo et al [14] proposed a data-driven approach based on long short-term memory (LSTM) to predict the sensor temperature for axle bearings. Besides, the prediction based on the back propagation (BP) neural network and LSTM network was conducted by researchers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [14] proposed a data-driven approach based on long short-term memory (LSTM) to predict the sensor temperature for axle bearings. Besides, the prediction based on the back propagation (BP) neural network and LSTM network was conducted by researchers [14][15][16]. A neural network predictive control scheme based on adaptive extended particle swarm optimization was also proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid development of machine learning algorithms has brought new possibilities for temperature prediction. For instance, Luo et al proposed a long short term memory-based approach to forecast the temperature trend [ 8 , 9 ]. In addition, many other methods based on temperature data have also been proposed [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%